COMPARISON OF LEVOBUPIVACAINE WITH TWO DIFFERENT ADJUVANTS (DEXAMETHASONE VS. DEXMEDETOMIDINE) IN ULTRASONOGRAPHY-GUIDED TRANSVERSUS ABDOMINIS PLANE BLOCK FOR UNILATERAL INGUINAL HERNIORRHAPHY: A RANDOMIZED DOUBLE-BLINDED CONTROL TRIAL - Partani, Seema; Karia, Swati; Sharma, Priyam; Sharma, Charu; Choudhary, Savita; Kumar, Anurag; Baweja, Yash; Chauhan , Vaishali (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Ultrasonography (USG)-guided transversus abdominis plane (TAP) block is an effective technique for postoperative analgesia in patients undergoing intraabdominal surgery. This study was aimed to compare the post-operative analgesia, hemodynamic variables, sedation, and adverse effects of levobupivacaine with two different adjuvants (dexamethasone and dexmedetomidine) in USG-guided TAP block for patients undergoing unilateral inguinal herniorrhaphy under subarachnoid block. Methods: A double-blind randomized control study, conducted on 96 patients, allocated in three groups of 32 each. Patients in group C received 0.25% levobupivacaine (20 mL) with normal saline (2 mL), group D1 received 0.25% levobupivacaine (20 mL) added with 0.1 mg/kg dexamethasone (2 mL) and group D2 received 0.25% levobupivacaine added with 0.5 mcg/kg dexmedetomidine diluted in NS (2 mL). Pain was assessed using Visual Analog Scale (VAS). The time for request of first analgesia (TFA), total number and total dose of rescue analgesic in 24 h were recorded. Statistical analysis was done using unpaired Student’s t-test and ANOVA. Results: At 12 and 24 h >30% of patients had VAS ≥4 in control group while it was <10% in groups D1 and D2 (p<0.001). TFA was earliest in control group (6.10±0.96 h) as compared to group D1 (7.26±1.22 h) and group D2 (7.49±1.02 h) (p<0.001). The total number and total dose of analgesic given were higher in the control group than other two groups (p<0.001). However, it was comparable between groups D1 and D2 (p<0.05). Conclusion: Dexamethasone and dexmedetomidine when added as an adjuvant to levobupivacaine for TAP significantly prolonged the duration of post-operative analgesia as compared to levobupivacaine alone, however, it was found to be comparable between adjuvant groups.